“Novo” Ensino Médio e trabalho pedagógico na rede estadual do Rio Grande do Sul: impactos na formação da força de trabalho no Brasil - Eichner, Ânthony Scapin (2023)
This Master's thesis, developed under the Kairós – Grupo de Estudos e Pesquisas sobre Trabalho, Educação e Políticas Públicas, was produced and oriented to respond to the following problematization: Based on the High School Reform in the state education network of Rio Grande do Sul (RS), what relationships can be established between the pedagogical work, aimed at training high school students, and the current stage of capitalist accumulation and its consequences for the reproduction of the workforce in Brazil? From this problematization, derive some research questions: What are the configurations of the current stage of capitalist accumulation? How do the current configurations of capitalism imply labor relations in Brazil? How is the “New” Secondary Education linked to the formation of the workforce in Brazil? How does carrying out the Reform guide pedagogical work in high school in the state of RS? The general objective is to analyse, based on the High School Reform in the state education network of Rio Grande do Sul, the relations between the pedagogical work, aimed at the training of secondary students, and the current stage of capitalist accumulation and its consequences for reproduction of the workforce in Brazil. The starting point was Historical-Dialectic Materialism, a Marxist approach to analysis and knowledge of social reality, which guided the research based on the assumption that production relations and class struggle, according to their current configurations, impact Brazilian educational policies. Procedurally, bibliographic research and document analysis were used as auxiliary instruments in working with data and in dissertation production. In general terms, it was found that the Secondary Education Reform, according to the singular implantation in the State of RS, expresses a need for reformulation in the training of the workforce, taking into account the current manifestation of overexploitation carried out in Brazil. The emphasis on skills, curriculum flexibility and the appearance of curricular components related to “practice”, to the detriment of “theoretical ones”, reveal an adaptation of student training to the current stage of capital accumulation on the periphery of capitalism. Workers graduated from public high schools are prepared for a dynamic of discarding, due to the quantitative increase in the industrial reserve army. The “new” High School is a consequence of the demand for a curriculum and pedagogical work that form an individualistic and meritocratic ideology, capable of making students learn to be flexible and adaptable and/or blame themselves for unemployment or precarious work, so common in the current context.